DIGITAL HEALTH AND ARTIFICIAL INTELLIGENCE IN HEALTHCARE: ETHICAL, CARE-BASED, AND ORGANIZATIONAL CHALLENGES IN MULTIPROFESSIONAL PRACTICE - Araújo, Amanda Martins; Sestari, Larissa Emanuelle; Lopes, Jander Marcus Cirino; Gomes, Aline de Morais; Farias, Daniel Alves; Florindo, Diogo Gabriel; Franco, Bruno Henrique da Silva; Carretilha, Arilana de Jesus; Sousa, Cleiton Mendes Honorato; Santos, Julio Gladston Ribeiro; Alves, Elda Lenilma Palheta; Mendes, Marcus Corrêa; et al. (Seven Editora, 2026)
The incorporation of Digital Health and Artificial Intelligence (AI) has promoted significant transformations in healthcare, influencing care practices, organizational processes, and clinical decision-making. In this context, multidisciplinary action plays a central role in ensuring that these technologies are used ethically, safely, and in line with patients’ needs. This study aimed to analyze the impacts of Digital Health and Artificial Intelligence on healthcare, with an emphasis on the ethical, care, and organizational challenges related to multidisciplinary action. This is a qualitative research study, developed through an analytical-interpretative approach based on recent scientific literature. The results indicate that AI, when integrated into collaborative practices, contributes to improving patient safety, shared decision-making, and care coordination at different levels of care. However, barriers related to professional training, technology governance, and the adaptation of work processes were also identified. It is concluded that the effectiveness of Digital Health and AI in healthcare depends on the articulation between technology, ethics, and interprofessional collaboration, reaffirming the leading role of the multidisciplinary team in building more integrated and humanized care models. DOI: https://doi.org/10.56238/sevened2026.002-015